Manufacture and Characterization of Heat Resistant and Insulating New Composites Based on Novolac Resin – Carbon Fibers – Perlite. Issue 1 (30th October 2013) - Kallergis, George; Pisania, Markella; Simitzis, Johannis
Summary: Multifunctional polymeric matrix composites combining proper mechanical properties with thermal insulating properties were manufactured. Such new composites consist of carbon fibers in low volume proportion (15% v/v), novolac resin as matrix, hexamethylenetetramine as curing agent and perlite as additive. The incorporation of 10% w/w perlite instead of the corresponding amount of novolac in these composites leads to lower density, and simultaneously the bending strength and shear strength remain constant. The coefficient of thermal conductivity indicates that these composites have thermal insulating properties.